2020
DOI: 10.1530/erc-19-0400
|View full text |Cite
|
Sign up to set email alerts
|

PRRT in high-grade gastroenteropancreatic neuroendocrine neoplasms (WHO G3)

Abstract: Peptide receptor radionuclide therapy (PRRT) is an established treatment for grade 1 and 2 gastroenteropancreatic neuroendocrine tumors with an increased uptake on somatostatin receptor imaging (SRI). Patients with metastatic high-grade (WHO G3) gastroenteropancreatic neuroendocrine neoplasms (NET G3 and NEC) represent a heterogeneous subgroup with poor prognosis and standard platinum-etoposide chemotherapy have limited therapeutic benefit. However, there is promising emerging evidence supporting the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 48 publications
0
81
0
2
Order By: Relevance
“…There is recent data in favor of PRRT as second or third-line treatment in GEP-NEN G−3. A review of four studies with more than 10 patients with NEN G−3 treated with PRRT was performed [84]. The majority of patients had a pancreatic tumor and 50% were well differentiated.…”
Section: Peptide Receptor Radionuclide Therapy (Prrt)mentioning
confidence: 99%
“…There is recent data in favor of PRRT as second or third-line treatment in GEP-NEN G−3. A review of four studies with more than 10 patients with NEN G−3 treated with PRRT was performed [84]. The majority of patients had a pancreatic tumor and 50% were well differentiated.…”
Section: Peptide Receptor Radionuclide Therapy (Prrt)mentioning
confidence: 99%
“…NETs in other studies [39,40]. Stratifying the PFS according to the grading, Sorbye et al [41] recently reported a PFS of 19…”
Section: Pathological Tissue Biomarkersmentioning
confidence: 98%
“…Coupled with 68 Ga-imaging ( Figure 10 ), it represents a powerful theranostic tool for the management of neuroendocrine tumors (NETs) [ 175 ]. Current research with [ 177 Lu]-DOTATATE aims to improve the safety and efficacy of this procedure, enlarge possible indication, notably in advanced, poorly-differentiated, GEP-NETs, [ 176 , 177 ] or other NETs, such as pheomochromocytoma or paraganglioma [ 178 , 179 ].…”
Section: Targeting Of Somatostatin Receptors With Radiopharmaceutimentioning
confidence: 99%